Glosa krytyczna do wyroku Sądu Apelacyjnego w Katowicach z dnia 22 czerwca 2022 r., I ACa 669/21. Podejmowanie uchwał na piśmie przez Walne Zgromadzenie Spółdzielni Mieszkaniowej - Pałka, Piotr (PRAWO i WIĘŹ, 2023)
The author believes that the provisions of Article 36 § 9-13 of the Co-operative Law concerning the possibility of ordering general assemblies to adopt resolutions in writing or using direct communication at a distance are also applicable to housing cooperatives, due to the wording of the provision of Article 1(7) of the Co-operative Law, according to which the provisions of the Co-operative Law are directly applicable to matters not regulated by the Act of Housing Cooperatives. Notwithstanding the above, the SA also seems to have completely ignored (iura novit curia) the wording of the uninterrupted provision of Article 15zzzr of the Act of 2 March 2020 on special solutions related to the prevention, prevention, and eradication of COVID-19, other infectious diseases, and crises caused by them, according to which a declaration of will of a member of a body of a legal person – and thus of the members of a housing cooperative who form a body such as the general assembly of the cooperative – other than the State Treasury or a local government unit, may be made in documentary form (and thus also in writing). Therefore, this provision should also be regarded as lex specialis to Article 83 of the Act on Housing Cooperatives.